Compact and stable SNAP ligand-conjugated quantum dots as a fluorescent probe for single-molecule imaging of dynein motor protein. Issue 80 (12th August 2015) - Ohyanagi, Tatsuya; Shima, Tomohiro; Okada, Yasushi; Tsukasaki, Yoshikazu; Komatsuzaki, Akihito; Tsuboi, Setsuko; Jin, Takashi
Abstract : Compact SNAP ligand-conjugated quantum dots (<10 nm) with high colloidal stability over a wide range of pH (5–9) are presented as a fluorescent probe for single-molecule imaging of dynein motor protein. Abstract : Compact SNAP ligand-conjugated quantum dots (<10 nm) with high colloidal stability over a wide range of pH (5–9) have been synthesized as fluorescent probe for the single-molecule imaging of dynein motor protein.